2010
DOI: 10.1177/0748233710364963
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium concentration in muscle, liver and kidney of sheep slaughtered in Falavarjan abattoir, Iran

Abstract: The aim of the present study was to investigate the levels of cadmium in sheep's muscle, liver and kidney from Isfahan and also to compare them with the levels reported in several other countries and with the maximum tolerance levels for the human consumption. The samples of muscle, liver and kidney of 60 animals around 1 to 6 years old were collected from the carcasses slaughtered in Flavarjan abattoir, Isfahan. Samples (acid digested and cadmium concentrations) were determined by graphite furnace atomic abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
2
1
Order By: Relevance
“…The lead levels found in this study were similar to most of the literature data as Al-Naemi, (2011) in Iraq, AbouDounia (2008) in Egypt, Kazemeini et al, (2010). Our result is in contrast with the ones found by of Nriagu et al (2009) in Jamaica; Khalafallah et al (2015); Bala et al (2013) in Niger, in which the limits are higher.…”
Section: Cadmiumsupporting
confidence: 88%
“…The lead levels found in this study were similar to most of the literature data as Al-Naemi, (2011) in Iraq, AbouDounia (2008) in Egypt, Kazemeini et al, (2010). Our result is in contrast with the ones found by of Nriagu et al (2009) in Jamaica; Khalafallah et al (2015); Bala et al (2013) in Niger, in which the limits are higher.…”
Section: Cadmiumsupporting
confidence: 88%
“…Gonzalez-Weller et al reported that Cd and Pb concentrations in meat products exceeded the recommended limits ( 17 ). Levels of Pb in buffalo muscles in the present study were lower than of Cd concentration in sheep muscles from Falavarjan abattoir, Iran ( 19 ).…”
Section: Discussioncontrasting
confidence: 65%
“…The ecosystem and environment are affected unfavourably by the soil degradation caused by heavy metal contaminants throughout the world [19][20][21]. Many health problems occur owing to the intense metal concentrations in soil which are absorbed by the growing plants resulting in food chain contamination [22][23][24].…”
Section: Introductionmentioning
confidence: 99%